Less is More: A Shortcut for Anionocages Design Based on (RPO32−)‐Monourea Coordination. Issue 41 (2nd September 2022) - Ma, Fen; Qiao, Xinrui; Zuo, Wei; Tao, Yu; Li, Anyang; Luo, Zhipeng; Liu, Yuqi; Liu, Xueru; Wang, Xiaoqing; Sun, Wei; Jia, Chuandong
Abstract: Anionocages have been developed as a unique family of hydrogen bonded cages. However, strategies for constructing anionocages are mainly limited to that based on (PO4 3− )‐bisurea coordination, neither the ligands nor the anions lack the simplicity and diversity of the maturely developed analogues based on metal coordination (i.e. metallocage). We report herein a more simple strategy for anionocages design based on (RPO3 2− )‐monourea coordination, utilizing monourea rather than bisurea as the hydrogen binding donor, and RPO3 2− rather than PO4 3− as the acceptor. Two fluorescent, quadruple helicate anionocages were constructed by a bis‐monourea ligand, and dianions PhOPO3 2− (H 1 ) or HOPO3 2− (H 1A ), respectively, which were capable of encapsulating a series of cation guests. As revealed by molecular modeling, H 1 features remarkable guest‐adaptive cavity breathing without change of the quadruple helicate topology, which allowed the encapsulation of different sized guests in an "induced fit" manner. Abstract : The convergent hydrogen bonding motif of phosphotyrosine residues of proteins has inspired an advanced strategy for the design of a new type of anionocage based on (RPO3 2− )‐monourea coordination, which features more simple synthesis and more potential of functionalization than the former strategy based on (PO4 3− )‐bisurea coordination, providing a proof of the design concept "Less is More".